Two-Dimensional Modeling of Leachate Distribution in Batu Layang Landfill on Peat Soil using Geoelectric Method - Fitriana Meilasari; Hendri Sutrisno; Arifin Arifin; Rizki Purnaini; Irda Dwi Utari (Universitas Diponegoro, 2023)
The open dumping system implemented by the Batu Layang landfill can produce leachate, contaminating groundwater around the landfill. Groundwater contaminated with leachate, if used by the community, can cause health problems. Therefore, management efforts were needed, such as subsurface leachate modeling. This study aims to model the distribution of subsurface leachate in 2 dimensions. The modeling of leachate distribution below the soil surface used the Wenner configuration geoelectric method. The number of geoelectric measurement paths was two paths. The length of each track was 195 m, with a distance of 5 m between the electrodes. Data obtained from resistivity values were analyzed using the Res2Dinv application. The calculation of leachate discharge used the water balance method. Based on the inversion results using the Res2Dinv software, the resistivity value of leachate-contaminated soil in line 1 was 1.19-9.43 Ωm, and track 2 was 0.5-10.2 Ωm. The leachate resistivity value was <10 Ωm because the leachate contains inorganic minerals (metals), so the resistivity value was low. Land contaminated with leachate was estimated to be spread as far as 195 m. The most profound leachate depth was estimated at 39.4 m. Batu Layang Landfill leachate discharge in Zone E averages 4 m3/day.